Determinants of Generation X’s Interest in Using QRIS as a Digital Payment Method in Jakarta: English - Azahra, Annisa; Pangestuty, Farah Wulandari (Contemporary Studies in Economic, Finance and Banking, 2026)
The development of the national digital payment system through QRIS has boosted transaction efficiency in Indonesia. However, its adoption rate among Generation X remains relatively low compared to younger generations, requiring an understanding of the factors that influence its use. This study aims to analyze the influence of perceived ease of use, perceived usefulness, trust, social influence, and financial literacy on Generation X's interest in using QRIS as a digital payment tool in DKI Jakarta. The research sample consisted of 160 respondents using a quantitative approach and the PLS-SEM method. The results showed that perceived ease of use had a significant negative effect on interest in using QRIS, but had a significant positive effect on perceived usefulness and had an indirect impact on interest in using QRIS through the mediating variable. Meanwhile, perceived usefulness and financial literacy have a significant positive effect on interest in using QRIS, while trust and social influence have no significant impact. These findings indicate that Generation X is more influenced by perceived benefits, financial literacy levels, and perceptions of usefulness based on ease of use in adopting QRIS, rather than by trust or social pressure. This study contributes theoretically by expanding the application of TAM in the context of national payment systems, as well as practically for governments and digital financial service providers in strengthening literacy and education on the benefits of QRIS for Generation X.